2006
DOI: 10.1002/nme.1791
|View full text |Cite
|
Sign up to set email alerts
|

Corotational non‐linear analysis of thin plates and shells using a new shell element

Abstract: SUMMARYA new three-node triangular shell element is developed by combining the optimal membrane element and discrete Kirchhoff triangle (DKT) plate bending element, and is modified for laminated composite plates and shells so as to include the membrane-bending coupling effect. Using appropriate shape functions for the bending and membrane modes of the element, the 'inconsistent' stress stiffness matrix is formulated and the tangent stiffness matrix is determined. Non-linear analysis of thin-walled structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 25 publications
0
60
0
1
Order By: Relevance
“…A 3-node triangular shell element can be formulated by combining a membrane element and a bending element [9][10][11][12], or by relying on three-dimensional continuum mechanics with the Reissner-Mindlin kinematic hypothesis and the plane-stress assumption [8,13]. Existing 3-node triangular shell elements can be categorized into 4 types: Type 1 with only 3 displacement degrees-of-freedom (dofs) per node [14][15][16][17][18][19][20][21][22]; Type 2 with 3 displacement dofs and 2 rotational dofs per node [23][24][25]; Type 3 with 3 displacement dofs at the vertices and the rotational dofs at side nodes [26][27]; Type 4 with 3 displacement dofs and 3 rotational dofs per node [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 3-node triangular shell element can be formulated by combining a membrane element and a bending element [9][10][11][12], or by relying on three-dimensional continuum mechanics with the Reissner-Mindlin kinematic hypothesis and the plane-stress assumption [8,13]. Existing 3-node triangular shell elements can be categorized into 4 types: Type 1 with only 3 displacement degrees-of-freedom (dofs) per node [14][15][16][17][18][19][20][21][22]; Type 2 with 3 displacement dofs and 2 rotational dofs per node [23][24][25]; Type 3 with 3 displacement dofs at the vertices and the rotational dofs at side nodes [26][27]; Type 4 with 3 displacement dofs and 3 rotational dofs per node [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…A flat shell element with 5 degrees-of-freedom per corner node can be obtained by combining a conventional triangular membrane element with a standard 9-dof triangular bending element. On the other hand, if several elements of this type sharing the same node are coplanar, it is difficult to achieve inter-element compatibility between membrane and transverse displacements, and the assembled global stiffness matrix is singular in shell analysis due to the absence of in-plane rotation degrees-of-freedom [9][10][11][12]34]. In addition, flat shell elements with 5 degrees-of-freedom per node lack proper nodal degrees of freedom to model folded plate/shell structures, making the assembly of elements troublesome [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before adopting IBM, we implemented a co-rotational treatment of the Discrete Kirchhoff Triangle [Batoz et al 1980;Khosravi et al 2007], but found that we needed a stronger guarantee of stability in the context of our interactive tool. We then adopted nonlinear hinges [Bridson et al 2003;Grinspun et al 2003], which lose some of the meshingindependence of DKT [Batoz et al 1980] but increase stability.…”
Section: Bendingmentioning
confidence: 99%
“…It is considered in several papers dealing with linear and nonlinear analysis of general shell structures (Bathe and Ho, 1981;Cook, 1993;Khosravi et al, 2007;Zhang et al, 2015). High-speed component impact analysis (Wu et al, 2005) demonstrates, for instance, that this element performs as good as the main element (Belytschko et al, 1984) used for crashworthiness analyses.…”
Section: Introductionmentioning
confidence: 99%